From Tears of Surrender to Anthems of Defiance: Assadi’s Poetic Triumph over Al-Jazzar in the Legacy of Adab al- Mu‘āraḍah" - Assadi, Jamal; Naamneh, Mahmoud; Sindawi, Khaled (Journal of Ecohumanism, 2025)
This article aligns with the tradition of Adab al-mu’āraḍah (opposition poetry), a significant genre in Arabic literature that fosters poetic dialogue through imitation, innovation, and critique. Originating in classical Arabic poetry, Adab al-Mu’āraḍah has been shaped by pioneers such as al-Mutanabbī, al-Buḥturī, and al-Ma‘arrī, who elevated the form by engaging with their contemporaries’ works. In modern times, poets like Ahmed Shawqī, Ḥāfiẓ Ibrāhīm, Mustafa Al-Jazzar, and Naseem Assadi have revitalized this tradition, addressing contemporary social and political issues while preserving its classical roots. This study focuses on two contemporary contributions to Adab al-Mu’āraḍah: Al-Jazzar’s “Wipe Your Tears and Retreat, O ʿAntarah” and Assadi’s “Gather Your Forces and Rise, O ʿAntarah.” These poems invoke the legendary figure of ʿAntarah ibn Shaddād to explore contrasting themes. Al-Jazzar’s work reflects resignation and despair, symbolizing societal defeat, while Assadi’s response emphasizes defiance and resilience, serving as a call to action. The article adopts a comparative approach to analyze the linguistic, structural, and sonic elements of these works, situating them within the broader context of Adab al-Mu’āraḍah. By reinterpreting ʿAntarah’s symbolic legacy, the poets bridge classical literary heritage with contemporary struggles, offering fresh insights into identity, resistance, and political agency. This research underscores the enduring relevance of opposition poetry, highlighting its dynamic evolution as a tool for cultural criticism and ideological engagement, and contributes to the ongoing discourse on modern Arabic literary traditions.